Electrochemotherapy as a new approach on pancreatic cancer and on liver metastases. (September 2015) - Tafuto, Salvatore; von Arx, Claudia; De Divitiis, Chiara; Tracey Maura, Claire; Palaia, Raffaele; Albino, Vittorio; Fusco, Roberta; Membrini, Massimo; Petrillo, Antonella; Granata, Vincenza; Izzo, Francesco; ,
Abstract: Electrochemotherapy is a local non-thermal treatment for cancer ablation. Currently, many studies and case report have investigated the differences in effectiveness of electrochemotherapy with respect to tumor type, chemotherapeutic drug, and route of drug administration. ESOPE trial validated standard operating procedures [SOP] for ECT using the Cliniporator device and demonstrated that ECT is a simple, highly efficacious, and cost-effective treatment of cutaneous and subcutaneous nodules from different primary tumors for cutaneous or superficial lesions. This review has the purpose to summarize current knowledge about clinical effectiveness of electrochemotherapy and future prospects regarding its use on pancreatic cancer and liver metastasis not only.